2017
DOI: 10.1371/journal.pone.0183395
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin E supplementation on uterine cervical neoplasm: A meta-analysis of case-control studies

Abstract: Several epidemiological studies have suggested that vitamin E could reduce the risk of uterine cervical neoplasm. However, controversial data were presented by different reports. Hence, we conducted a meta-analysis to assess the relationship between vitamin E and the risk of cervical neoplasia. We performed a comprehensive search of the PubMed, Embase and Cochrane databases through December 31, 2016. Based on a fixed-effects or random-effects model, the odds ratio (OR) and 95% confidence intervals (CIs) were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 40 publications
0
20
0
1
Order By: Relevance
“…Higher VE intake was found to be associated with a lower risk of invasive cervical cancer in a case‐control study in China 59 . This finding was corroborated in a meta‐analysis that involved 15 case‐control studies and found an inverse relationship between VE intake and cervical cancer 79 . Also, in meta‐analyses, inverse associations were observed between serum levels of α‐T and breast cancer risk by Hu et al 80 as well as renal cancer by Shang et al 81 and Shen et al 82 In the combined Shanghai Women's and Men's Health Studies, dietary VE intake (including supplements) was inversely associated with liver cancer risk 60 .…”
Section: Human Studies On Ve and Cancermentioning
confidence: 56%
See 3 more Smart Citations
“…Higher VE intake was found to be associated with a lower risk of invasive cervical cancer in a case‐control study in China 59 . This finding was corroborated in a meta‐analysis that involved 15 case‐control studies and found an inverse relationship between VE intake and cervical cancer 79 . Also, in meta‐analyses, inverse associations were observed between serum levels of α‐T and breast cancer risk by Hu et al 80 as well as renal cancer by Shang et al 81 and Shen et al 82 In the combined Shanghai Women's and Men's Health Studies, dietary VE intake (including supplements) was inversely associated with liver cancer risk 60 .…”
Section: Human Studies On Ve and Cancermentioning
confidence: 56%
“…In a meta‐analysis of 69 prospective studies by Aune et al, 84 even though there was no relevant link between dietary VE intake and cancer incidence or total mortality, an increase of 5 µg/mL in serum α‐T level was linked to a 9% or 6% decrease in total cancer rate or total mortality rate, respectively. Meta‐analysis that focused on serum VE levels were more likely to find an inverse association 75,76,79,80 . Genetic SNP's that resulted in an increase of serum α‐T levels were shown to be associated with a decrease in cancer risk 43,44 .…”
Section: Human Studies On Ve and Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Ehiozogie Obhielo 1 , Michael Ezeanochie 2 *, Oghenefegor Olokor O 2 , Anthony Okonkwo 2 , Etedafe Gharoro 2 component of the intracellular antioxidant glutathione peroxidise enzyme has been shown from several lines of evidence to have a protective effect against cancer development (Cunzhi et al, 2003;Kim et al, 2003). Recent studies suggest that risk of premalignant disease of the cervix increases with decreasing serum antioxidant system activity and reduced serum levels of micronutrients such as selenium and Vitamin E (Kim et al, 2003;Hu et al, 2017).…”
Section: The Relationship Between the Serum Level Of Selenium And Cermentioning
confidence: 99%